2009
DOI: 10.1177/1934578x0900400205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cryptolepine and Huperzine Derivatives as Lead Compounds towards New Agents for the Treatment of Human African Trypanosomiasis

Abstract: The alkaloid cryptolepine (1) and eight synthetic analogues (2-8) were assessed for in vitro activities against Trypanosoma brucei. Four of the analogues were found to be highly potent with IC 50 values of less than 3 nM and three of these were assessed against T. brucei brucei infection in rats. The most effective compound was 2, 7-dibromocryptolepine (7); a single oral dose of 20 mg/kg suppressed parasitaemia and increased the mean survival time to 13.6 days compared with 8.4 days for untreated controls. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Previously, a substantial augmentation in the activity of the analogue 8 against Plasmodium falciparum and T. b. brucei (Wright et al 2001;Oluwafemi et al 2009) has been reported. Presently, we have observed a dramatic increase in antileishmanial potential of 8, with bromo-substituents at both 2 and 7 positions, in comparison to either the 2-bromo-(3), or the 7-bromo-(4) analogues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a substantial augmentation in the activity of the analogue 8 against Plasmodium falciparum and T. b. brucei (Wright et al 2001;Oluwafemi et al 2009) has been reported. Presently, we have observed a dramatic increase in antileishmanial potential of 8, with bromo-substituents at both 2 and 7 positions, in comparison to either the 2-bromo-(3), or the 7-bromo-(4) analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Several halogenated derivatives of 1 were found to be considerably more potent than 1 and exhibited promising in vivo activity against Plasmodium berghei, the rodent malaria parasite (Onyeibor et al 2005). Again, the analogues like 2-chlorocryptolepine (5), 8-chlorocryptolepine (6), 7-bromocryptolepine (4), and 2, 7-dibromocryptolepine (8), have also been shown to be active against Trypanosoma brucei brucei, the causative parasite for African sleeping sickness (Oluwafemi et al 2009). Hence, it was considered worthwhile to investigate some of the cryptolepine analogues vis-à-vis cryptolepine against L. donovani, the related parasite causing visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 97%
“…In infected mice with P. berghei, the 2-chloro-7-bromo (30k) suppressed parasitemia by 90% at doses of 25 mg.kg -1 .day -1 , with no apparent toxicity to the mice. Like previously, the authors hypothesized that the mechanism of action of these compounds could be by inhibition of hemozoin formation in the food vacuole, however, no correlation between antiplasmodial activity and accumulation in the acid food vacuole, determined by a mathematical equation based on compounds pK a , was seen, suggesting that the antimalarial activity involves other mechanisms in addition to the inhibition of hemozoin formation [51,93]. Recently, Oluwafemi and coworkers evaluated the activity of 29n-t against T. brucei and four analogues were found to be highly potent (29o-q,s) when compared with 1 (IC 50 = 306 nM) [93].…”
Section: Antiprotozoal Activitymentioning
confidence: 89%
“…We recently reported that huprine Y ( 1 , Fig. 1), a 7-chloro-4-aminoquinoline derivative with potent acetylcholinesterase (AChE) inhibitory activity, developed in our group as an anti-Alzheimer drug candidate, 28 exhibited significant activity against T. brucei (IC 50  = 0.61 μM, selectivity index (SI) over rat myoblast L6 cells = 13) 29, 30. In 4-aminoquinoline-based antimalarials, both dimerization and side chain modification have been used to increase potency and overcome parasite resistance 31, 32, 33, 34, 35.…”
Section: Introductionmentioning
confidence: 99%